Alpha-glucosidase inhibitory activity of a tablet formulated from Chrysophyllum cainito L. (Fam. Sapotaceae) leaves extract - Casimpan, Guinevere A.​; Castro, Kimberly P.​; Eñano, Khristelle C.​; Ladignon, Ethel Andrea C. (​​​​​​​​​​Manila: Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
Diabetes remains a global threat, with the Philippines as one of its emerging hotspots. Alpha-glucosidase inhibitors are recommended as first?line therapy and Chrysophyllum cainito leaves have a great potential in having this activity. However,it has no available dosage forms yet. Thus, this study aims to evaluate the alpha-glucosidase inhibitory activity of a tablet formulated from C. cainito leaves extract. The milled sample was collected from a farm in Negros Occidental,Philippines. Cold maceration process using distilled water and subsequent evaporation to dryness were done to obtain the crude extract. The crude extract was re-dissolved and fumed silica was added. The mixture was lyophilized and the resulting powder acted as the active ingredient. This was formulated into a tablet via direct compression method. The drug-excipient compatibility study results suggest that acidic excipients should not be used in the formulation. Both the crude extract and the tablet had undergone alpha?glucosidase inhibitory bioassay. It was found that there is only a minor difference between the inhibitory activity of the crude extract (1C50= 116.78 ug/mL)and that of the tablet (1C50= 121.1l ug/mL). Additional formulation and bioassay trials are recommended to conduct statistical analysis.
Available to the general public.
​​​​​​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines Manila, May 2017. ​
Keywords: Sapotaceae; Plant extracts; Glucosidase inhibitors